Implementasi Prinsip Good Corporate Governance Terhadap Kinerja Karyawan Pada Bank Syariah - Amanda Putri, Maya; Agnik, Erika Dwi; Djasuli, Mohamad (Jurnal Ekonomika Dan Bisnis (JEBS), 2022)
The purpose of this study is to analyze the application of good corporate governance (GCG) in the work of Bank BRISsyariah Indonesia employees. The application of good governance in the banking sector is very supportive for the implementation of its operational activities, if banking is the trust of the public who trust their investment managers, then very careful risk management is needed to create a positive image of banking. sector In the eyes of customers, the role of banking is also to provide confidence in collecting and saving money. This study uses a descriptive qualitative approach which aims to provide a systematic description of the implementation of good corporate governance practices at Bank BRISyariah. The purpose of data analysis is to simplify the results of data processing so that they are easy to read and interpret. Data was collected using the literature review technique. The results of this study indicate that the good governance practices implemented by Bank BRISyariah Indonesia are largely in line with the theory of good governance.